Global, regional, and national burden of upper respiratory infections, 1990–2021: findings from the Global Burden of Disease study 2021 - Shun-Xian Zhang; Yu-Juan Liu; En-Li Tan; Guo-Bing Yang; Yu Wang; Xiao-Jie Hu; Ming-Zi Li; Lei Duan; Shan Lv; Li-Guang Tian; Mu-Xin Chen; Fan-Na Wei; et al. (Science in One Health)
Background: Upper respiratory infections (URIs) are common infectious diseases worldwide. Accurate and timely assessment of the disease burden of URIs is crucial for governments to develop comprehensive prevention and control strategies, and to allocate and utilize healthcare resources more efficiently. Methods: For URIs in Global Burden of Disease (GBD) 2021 database, age-standardized incidence rates (ASIR), age-standardized prevalence rates (ASPR), age-standardized mortality rates (ASMR), disability-adjusted life-years (DALYs), and case numbers for incidence, prevalence, deaths, and DALYs across the globe, five socio-demographic index (SDI) regions, 21 geographical regions, and 204 countries and territories were provided and analyzed. Trends from 1990 to 2021 were described using the average annual percentage change (AAPC), and future URIs burden was projected with a Bayesian age-period-cohort (BAPC) model. Results: From 1990 to 2021, there was a significant decline in global ASIR (APCC = −289.86, 95% confidence interval [CI]: −298.59 to −281.12), ASPR (AAPC = −4.04, 95% CI: −4.16 to −3.92), ASMR (AAPC = −0.02, 95 % CI: −0.02 to −0.03) and age-standardized DALY rate (AAPC = −0.75, 95% CI: −0.76 to −0.74). The ASIR, ASPR, ASMR, and age-standardized DALY rate were high in elderly for both males and females, and both genders. Similarly, the number of incident cases, prevalence cases, deaths, and DALY cases for URIs was highest in children under five years. The ASMR and age-standardized DALY rate exhibited a negative correlation with SDI across 204 countries and territories in 2021. The ASIR and ASPR for URIs will show an upward trend from 2022 to 2050, while ASMR and age-standardized DALY rate are expected to decline. Low birth weight for gestation remains the leading contributor to deaths related to URIs. Conclusion: Despite the global decline in URIs burden, significant challenges remain among the elderly population. These findings support the optimization and implementation of public health policies, including targeted vaccination and integrated One Health approaches to reduce the burden in high-risk populations.